MENINGKATKAN HASIL BELAJAR LEMPAR TURBO DENGAN MODIFIKASI ALAT PADA SISWA KELAS V SDN KARANGGUPITO 1 KENDAL NGAWI TAHUN PELAJARAN 2022/2023 - Al Mubarok, Mohammad Wildan; Prayoga, Aba Sandi; Bayu Utomo, Andy Widhiya (Jurnal Porkes, 2024)
This research aims to determine the effect of learning modification tools on turbo throwing learning outcomes. Turbo throwing is a technique in athletic sports games, namely the activity of throwing with one hand to reach a certain distance. Based on observations made at sdn karanggupito 1 kendal ngawi, there were problems experienced by students in the learning process of physical education, sports and health. Practical results are still low, namely not meeting the minimum completeness criteria (kkm) of 75. Like in class v, which has 14 students, many of them have not met the kkm. Of which 2 students got a score >75, and 12 students got a score <75. This means that 86% of those who have not met the minimum completion criteria (kkm) in class v are 86% and only 14% have passed. By learning using this modified tool, it can improve student learning outcomes from psychomotor, affective and cognitive aspects, and can improve the quality of learning. From this research, it was stated that an increase in learning outcomes for turbo throwing was 50% in cycle i and 86% in cycle ii and that learning completeness (meeting the kkm) could be successfully carried out with alminimum completion requirement of 80% of the number of students.